Prevalence, Theoretical Framework and South African Legislative Measures on Child Sexual Abuse and Incest - Smit, Elizabeth Ivy (Technium Social Sciences Journal, 2021)
Background Child sexual abuse and incest are the worst crimes and offences against children and the vulnerable in the society. These have continued to plague South African communities and a major social issue for social workers. The study drew from previous findings on psycho-social effects of father-daughter incest which was conducted in fulfilment of a Masters studies. As well as how it affected the offender and the family. Objectives and Purpose of the study The study attempted to understand how incest manifest within and across nations, how the family is affected and what role it plays in an incestuous relationship as well the sanctioning of such social abomination. Social Work intervention is also scrutinize particularly in support of the family. Methods The study emanates from a Masters research undertaken where qualitative approach was utilized to determine psycho social effects of incest. This piece of work looked at the prevalence and nature of incest, theoretical framework in respect of incest as well as South African punitive measures on child sexual abuse and incest. These were discussed as themes with subthemes.